POLITICS OF EDUCATION: EFFECT ON GOVERNMENT POLICIES AND PROGRAMMES' IMPLEMENTATION IN PUBLIC SECONDARY SCHOOLS IN IKOM EDUCATION ZONE OF CROSS RIVER STATE - Charles Ekpung Ekpung; Tiku Ebam; Anietie Imo Imo (PT. Antis International Publisher, 2025)
Objective: This study investigates the influence of politics on the implementation of government educational policies and programmes in public secondary schools in Ikom Education Zone of Cross River State, Nigeria, with emphasis on political interference, favoritism, corruption, and inequitable resource allocation. Method: A descriptive survey design was employed, drawing from a population of 1,487 teachers, 115 principals, and 38 school supervisors. A stratified and purposive sample of 150 respondents (90 teachers, 45 principals, and 15 supervisors) was selected. Data were gathered through questionnaires, interviews, and document analysis, and analyzed using descriptive statistics, chi-square tests, regression analysis, and thematic interpretation. Results: The findings revealed that political interference disrupts policy implementation, influences teacher deployment and administrative appointments, and creates disparities in resource distribution. Furthermore, corruption and patronage hinder programme effectiveness, while politically favored schools benefit disproportionately from infrastructure and resources. Novelty: The study provides empirical evidence linking political dynamics directly to the success or failure of educational policies in Nigeria, underscoring the urgent need for depoliticized governance, equitable distribution of resources, and strengthened accountability systems to promote sustainable educational development.